Tim Travers and the time traveler's paradox [videorecording (DVD)] - Dunning, Samuel; Day, Felicia, 1979-; David, Keith (Mill Creek Entertainment, 2025)
Tim Travers, Penniless Genius Ostricized Narcissist, invents a time machine to travel back and kill his younger self and unmake reality. When his plan fails, he discovers something even more terrifying: Himself.